Automatic Cleaning System Design to Increase PV Panel Output Power - Muhammad Zulfahmi; RD Kusumanto; Yohandri Bow (International Journal of Research in Vocational Studies (IJRVOCAS), 2021)
The existence of the Township Housing, which is currently near the coal mine site, precisely in Tanjung Enim, South Sumatra, with a relatively open area (41 Ha) and a relatively high elevation of approximately 100 meters over the sea level, has the potential to be installed with PV panels as a solar power plant. Installation of PV panels in residential areas close to coal mining activities has the potential to indirectly generate a lot of mine dust which can reduce the amount of light received by the PV panels, which in turn can affect the output power of the PV panels. The purpose of this study is to analyze the use of an automatic cleaning system to increase the output power of PV panels by comparing the output power of PV panels produced between PV panels with an automatic cleaning system in the form of a water sprayer with PV panels that are not equipped with a water sprayer (standard PV installation). The use of an automatic cleaning system shows an increase in the average output power of 44.56 Watt. The difference between Isc PV water sprayer and normal PV is 0.5513 A. Iload measurement on PV water sprayer is 0.1973 A higher than normal PV, while for VOC PV panel water sprayer is smaller than normal PV is about 0.45 V. For PV water sprayer Vload is 0.431 V is more significant than normal PV panels. Meanwhile, for the generated load power or Pload, the PV water sprayer is 9.47 watts higher than normal PV. From all these values, the average efficiency produced by PV water sprayer is 1.81% greater than the efficiency produced by normal PV. This study shows that PV using a water sprayer produces an average output power of 44.56 watts